Master of Christmas Trees - Stern, Niels (Nordlyd, 2026)
The article describes the highly collaborative process of the creation of policy recommendations for Open Access books within the EU-funded project PALOMERA (Policy Alignment of Open access Monographs in the European Research Area). Johan Rooryck played a leading role in this specific project task. Extensive stakeholder involvement and iterative validation exercises ensured greater recommendation alignment and created community engagement, which in their turn increase the recommendations’ chances for being implemented. The recommendations are an important stepping stone for the policy development of open and equitable academic book publishing.
Keywords: Open Access books; policy; PALOMERA; community; stakeholder involvement; co-creation